Wybiórczość siedliskowa żuka leśnego Anoplotrupes stercorosus (Scriba) i żuka wiosennego Trypocopris vernalis (L.) (Coleoptera: Geotrupidae) w borze sosnowym świeżym w zależności od wieku drzewostanu - Marczak, Dawid (Leśne Prace Badawcze, 2013)
In Poland, Anoplotrupes stercorosus (Scriba) and Trypocopris vernalis (L.), are very common throughout the whole country and belong to the most numerous representatives of the Geotrupidae family. Research on the habitat selectivity of Anoplotrupes stercorosus (Scriba) and Trypocopris vernalis (L.) was conducted in the years 2004-2006 in the Wipsowo Forest Inspectorate (Regional Forest Department in Olsztyn). The dung beetles were collected using Barber traps installed in a clear-cut comprising, 2, 3, 5, 8, and 16 year old thickets and tree-stands aged 30, 45, 60, 80, 100 and 135 years. According to phytosociology these tree-stands are a plant community of fresh continental pine forest ( Peucedano-Pinetum ), while typologically all sites are within the fresh coniferous forest. During the course of this research 29197 individual dung beetles were captured, including 23137 individuals of A. stercorosus and 6060 individuals of T. vernalis . Both species were caught at each research site. At nearly all sites A. stercorosus dominated. Only within the clear-cut area were the number of T. vernalis was higher than at other sites. Very many individuals of T. vernalis were present in the clear-cut area but their numbers decreased gradually with increasing tree-stand age. An opposite situation was noted for A. stercorosus . There was an interesting statistically-significant decrease in the abundance of both species in the middle-aged tree-stands – 30, 45 and 60-year-old. Analyzing the seasonal dynamics revealed one peak in the population of T. vernalis in July, whereas there were two peaks in the population of A. stercorosus : a small peak in July and a much larger peak in September. There was a significant negative correlation between the numbers of T. vernalis and tree-stand age (p